Faktor-Faktor yang Mempengaruhi Integritas Laporan Keuangan:Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2021 - Nurhayati Nurhayati; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of company size, audit quality and good corporate governance on integrity of financial report. The data used is secondary data in the form of an annual report of property and real estate companies listed on the Indonesia Stock Exchange for 6 years of observation, from 2016 to 2021. The sample was determined by purposive sampling technique and then resulted in 19 companies as the sample. This research used multiple linear regression analysis models. The results of this study showed that company size and audit committee have a positive and significant effect on integrity of financial report. Meanwhile, audit quality and the elements of corporate governance of independent commisioner, and institutional ownership have no significant effect on integrity of financial report as measured using model beaver and ryan with ratio MBV.